Proving Skip: "(SKIP,s)⇒ s" terminates in Isabelle - terminate

How can I show that
"(SKIP,s)⇒ s",
which is a rule of the Big Step Semantics, terminates in Isabelle?
Big Step Semantics is defined as follows "(SKIP,s)⇒ s" is one command.
inductive big_step :: "com × state ⇒ state ⇒ bool" where
Skip: "(SKIP,s) ⇒ s" |
Assign: "(x ::= a,s) ⇒ s(x := aval a s)" |
Seq: "⟦ (c⇩1,s⇩1) ⇒ s⇩2; (c⇩2,s⇩2) ⇒ s⇩3 ⟧ ⟹ (c⇩1;;c⇩2, s⇩1) ⇒ s⇩3" |
IfTrue: "⟦ bval b s; (c⇩1,s) ⇒ t ⟧ ⟹ (IF b THEN c⇩1 ELSE c⇩2, s) ⇒ t" |
IfFalse: "⟦ ¬bval b s; (c⇩2,s) ⇒ t ⟧ ⟹ (IF b THEN c⇩1 ELSE c⇩2, s) ⇒ t" |
I used the formal definition for total correctness
⊫ {P} c {Q} ≡ ∀s. P s ⟶ (∃ t. (c, s) ⇒ t ∧ Q t)
so that my Lemma now has the following form:
lemma "skip: {P} skip {Q} ≡ ∀s. P s ⟶ (∃ t. (skip, s) ⇒ t ∧ Q t)"
Is that definition of the Lemma correct to show that it terminates?

Related

How to prove the Equivalence of two object of (proj1_sig f a) and (proj1_sig f b), where a and b are Equivalent

I am trying to prove that given
(eqX : relation X) (Hypo : Equivalence eqX) (f : X -> {x : X | P x})
then
eqX a b -> eqX (proj1_sig (f a)) (proj1_sig (f b))
The function f get a parameter of Type X and give an existing assertion {x : X | P x}. ( for example fun (n : nat) => {m : nat | S m = n} )
In one word, I would like to show that given two parameters which are equivalent under the equivalent relation eqX, then the destruct result of existing assertion {x : X | P x} is also of the same equivalence class.
Can I prove this goal directly(which means the Specif.sig hold this property), or I should prove or claim that f satisfy some constraint and after which can I get this assertion proven.
Your claim is not directly provable; consider
X := nat
eqX a b := (a mod 2) = (b mod 2)
P a := True
f x := exist P (x / 2) I
Then we have eqX 2 4 but we don't have eqX (proj1_sig (f 2)) (proj1_sig (f 4)) because we don't have eqX 1 2.
You can either take in the theorem you are trying to prove as a hypothesis, or you can take in a hypothesis of type forall a, proj1_sig (f a) = a, or you can take in a hypothesis of type forall a, eqX (proj1_sig (f a)) a. Note that all of these are provable (by reflexivity or intros; assumption) if you have f a := exist P a (g a) for some function g.
Is this what you are trying to show?
Require Import Coq.Relations.Relation_Definitions.
Require Import Coq.Classes.Equivalence.
Require Import Setoid.
Generalizable All Variables.
Lemma foo `{!#Equivalence A RA, #Equivalence B RB, f : #respecting A _ _ B _ _ , #equiv A _ _ a b} :
equiv (proj1_sig f a) (proj1_sig f b).
Proof.
now apply respecting_equiv.
Qed.

Haskell correct types for class and instance

I am struggling to describe what it means for terms and literals (first order logic) to be re-written. Ie I would like a function applySubstitution that can be called on both terms and literals.
I thought that the substitution could be expressed as a function. However I am getting rigid type variable errors with the following code.
{-# LANGUAGE UnicodeSyntax #-}
module Miniexample where
import qualified Data.Maybe as M
data Term a = F a [Term a]
| V a
data Literal a = P a [Term a]
| E (Term a) (Term a)
class Substitutable b where
substitute :: b -> (Term a -> Maybe (Term a)) -> b
instance Substitutable (Term a) where
substitute x#(V _) σ = M.fromMaybe x (σ x)
substitute f#(F l xs) σ = M.fromMaybe f' (σ f)
where f' = F l (map (flip substitute σ) xs)
instance Substitutable (Literal a) where
substitute (P l xs) σ = P l (map (flip substitute σ) xs)
substitute (E s t) σ = E (substitute s σ) (substitute t σ)
class Substitution σ where
asSub :: σ -> (a -> Maybe a)
applySubstitution σ t = substitute t (asSub σ)
(<|) t σ = applySubstitution σ t
This gives be the following error:
• Couldn't match type ‘a1’ with ‘a’
‘a1’ is a rigid type variable bound by
the type signature for:
substitute :: forall a1.
Term a -> (Term a1 -> Maybe (Term a1)) -> Term a
at /.../Miniexample.hs:16:3-12
‘a’ is a rigid type variable bound by
the instance declaration
at /.../Miniexample.hs:15:10-31
Expected type: Term a1
Actual type: Term a
• In the first argument of ‘σ’, namely ‘x’
In the second argument of ‘M.fromMaybe’, namely ‘(σ x)’
In the expression: M.fromMaybe x (σ x)
• Relevant bindings include
σ :: Term a1 -> Maybe (Term a1)
(bound at /.../Miniexample.hs:16:22)
x :: Term a
(bound at /.../Miniexample.hs:16:14)
substitute :: Term a -> (Term a1 -> Maybe (Term a1)) -> Term a
(bound at /.../Miniexample.hs:16:3)
In my head, the type variable b in the Substitutable class should be able to take on (bad terminology I'm sure) the the value of Term a.
Any hints would be greatly welcome.
To give a more concrete example, the following works, but one needs to be explicit about which function applyTermSub or applyLitSub to call and secondly the implementation of the substitution map leaks into the implementation of the more general procedure.
module Miniexample where
import qualified Data.Maybe as M
import qualified Data.List as L
data Term a = F a [Term a]
| V a deriving (Eq)
data Literal a = P a [Term a]
| E (Term a) (Term a) deriving (Eq)
termSubstitute :: (Term a -> Maybe (Term a)) -> Term a -> Term a
termSubstitute σ x#(V _) = M.fromMaybe x (σ x)
termSubstitute σ f#(F l xs) = M.fromMaybe f' (σ f)
where f' = F l (map (termSubstitute σ) xs)
litSubstitute :: (Term a -> Maybe (Term a)) -> Literal a -> Literal a
litSubstitute σ (P l xs) = P l (map (termSubstitute σ) xs)
litSubstitute σ (E s t) = E (termSubstitute σ s) (termSubstitute σ t)
applyTermSub :: (Eq a) => Term a -> [(Term a, Term a)] -> Term a
applyTermSub t σ = termSubstitute (flip L.lookup σ) t
applyLitSub :: (Eq a) => Literal a -> [(Term a, Term a)] -> Literal a
applyLitSub l σ = litSubstitute (flip L.lookup σ) l
-- variables
x = V "x"
y = V "y"
-- constants
a = F "a" []
b = F "b" []
-- functions
fa = F "f" [a]
fx = F "f" [x]
σ = [(x,y), (fx, fa)]
test = (applyLitSub (P "p" [x, b, fx]) σ) == (P "p" [y, b, fa])
Ideally I would like to have an interface for substitutions (i.e one could use Data.Map etc) and secondly I would like a single substitute function that captures both term and literals.
The error you're getting is a complaint that Term a, as specified in instance Substitutable (Term a), is not the same type as the Term a that σ accepts. This is because Haskell quantifies a over the substitute function, but not over the rest of the instance definition. So an implementation of substitute must accept a σ that handles Term a1 for some value of a1, which is not guaranteed to be the specific a that your instance is defined on. (Yes, your instance is defined over all a... but from inside the scope of the instance definition, it's as if a specific a has been chosen.)
You can avoid this by parameterizing your Substitutable class by a type constructor instead of just a type, and passing the same a to that type constructor as is used in the σ type.
{-# LANGUAGE UnicodeSyntax #-}
import qualified Data.Maybe as M
import qualified Data.List as L
data Term a = F a [Term a]
| V a deriving (Eq)
data Literal a = P a [Term a]
| E (Term a) (Term a) deriving (Eq)
class Substitutable f where
substitute :: f a -> (Term a -> Maybe (Term a)) -> f a
instance Substitutable Term where
substitute x#(V _) σ = M.fromMaybe x (σ x)
substitute f#(F l xs) σ = M.fromMaybe f' (σ f)
where f' = F l (map (flip substitute σ) xs)
instance Substitutable Literal where
substitute (P l xs) σ = P l (map (flip substitute σ) xs)
substitute (E s t) σ = E (substitute s σ) (substitute t σ)
(<|) t σ = substitute t $ flip L.lookup σ
-- variables
x = V "x"
y = V "y"
-- constants
a = F "a" []
b = F "b" []
-- functions
fa = F "f" [a]
fx = F "f" [x]
σ = [(x,y), (fx, fa)]
main = print $ show $ (P "p" [x, b, fx] <| σ) == P "p" [y, b, fa]

Non-dependent list type Coq

I'm trying to define a non-dependent list type in Coq, but I cannot figure out a way to do that. I managed to define ndList axiomatically, modifying Coq's list definition. Here's my work so far:
Axiom ndList : forall C: Type, Type.
Axiom nil : forall C, ndList C.
Axiom cons : forall C, forall (c: C) (l: ndList C), ndList C.
Arguments nil {_}.
Arguments cons {_} _ _.
Axiom el : forall (C L: Type), forall (a: L) (s: ndList C)
(l: forall (x: C) (z: L), L), L.
Axiom c1 : forall (C L: Type), forall (a: L) (l: forall (x: C) (z: L), L),
el C L a nil l = a.
Axiom c2 : forall (C L: Type), forall (s: ndList C) (c: C) (a: L)
(l: forall (x: C) (z: L), L),
el C L a (cons c s) l = l c (el C L a s l).
Axiom c_eta : forall (C L: Type), forall (a: L) (l: forall (x: C) (z: L), L)
(t: forall y: ndList C, L) (s: ndList C) (eq1: t nil = a)
(eq2: forall (x: C) (z: ndList C), t (cons x z) = l x (t z)),
el C L a s l = t s.
Is there a way to define ndList as an Inductive type?
Thanks for helping.
Your "non-dependent" list type is provably isomorphic to Coq's list type:
Axiom ndList : forall C: Type, Type.
Axiom nil : forall C, ndList C.
Axiom cons : forall C, forall (c: C) (l: ndList C), ndList C.
Arguments nil {_}.
Arguments cons {_} _ _.
Axiom el : forall (C L: Type), forall (a: L) (s: ndList C)
(l: forall (x: C) (z: L), L), L.
Axiom c1 : forall (C L: Type), forall (a: L) (l: forall (x: C) (z: L), L),
el C L a nil l = a.
Axiom c2 : forall (C L: Type), forall (s: ndList C) (c: C) (a: L)
(l: forall (x: C) (z: L), L),
el C L a (cons c s) l = l c (el C L a s l).
Axiom c_eta : forall (C L: Type), forall (a: L) (l: forall (x: C) (z: L), L)
(t: forall y: ndList C, L) (s: ndList C) (eq1: t nil = a)
(eq2: forall (x: C) (z: ndList C), t (cons x z) = l x (t z)),
el C L a s l = t s.
Section iso.
Context {A : Type}.
Definition list_to_ndList : list A -> ndList A
:= list_rect (fun _ => ndList A)
nil
(fun x _ xs => cons x xs).
Definition ndList_to_list (ls : ndList A) : list A
:= el A (list A)
Datatypes.nil
ls
Datatypes.cons.
Lemma list_eq (ls : list A) : ndList_to_list (list_to_ndList ls) = ls.
Proof.
unfold ndList_to_list, list_to_ndList.
induction ls as [|x xs IHxs];
repeat first [ progress simpl
| progress rewrite ?c1, ?c2
| congruence ].
Qed.
Lemma ndList_eq (ls : ndList A) : list_to_ndList (ndList_to_list ls) = ls.
Proof.
unfold ndList_to_list, list_to_ndList.
transitivity (el A (ndList A) nil ls cons); [ symmetry | ]; revert ls;
match goal with
| [ |- forall ls, #?LHS ls = #?RHS ls ]
=> intro ls; apply (c_eta _ _ _ _ RHS ls)
end;
repeat first [ progress simpl
| progress intros
| progress rewrite ?c1, ?c2
| congruence ].
Qed.
End iso.
You can also easily get your el about lists, automatically, even:
Scheme el := Minimality for list Sort Type.
Check el. (* forall A P : Type, P -> (A -> list A -> P -> P) -> list A -> P *)
Does this suffice for your purposes, or are you wanting more?

Establish isomorphism between sigma of a prod and disjoint sum

I defined a Boole inductive type based on the disjoint sum's definition:
Inductive Boole :=
| inlb (a: unit)
| inrb (b: unit).
Given two types A and B I'm trying to prove the ismorphism between
sigT (fun x: Boole => prod ((eq x (inrb tt)) -> A) (eq x (inlb tt) -> B))
and
A + B
I managed to prove one side of the isomorphism
Definition sum_to_sigT {A} {B} (z: A + B) :
sigT (fun x: Boole => prod ((eq x (inrb tt)) -> A) (eq x (inlb tt) -> B)).
Proof.
case z.
move=> a.
exists (inrb tt).
rewrite //=.
move=> b.
exists (inlb tt).
rewrite //=.
Defined.
Lemma eq_inla_inltt (a: unit) : eq (inlb a) (inlb tt).
Proof.
by case a.
Qed.
Lemma eq_inra_inrtt (a: unit) : eq (inrb a) (inrb tt).
Proof.
by case a.
Qed.
Definition sigT_to_sum {A} {B}
(w: sigT (fun x: Boole => prod ((eq x (inrb tt)) -> A) (eq x (inlb tt) -> B))) :
A + B.
Proof.
destruct w.
destruct p.
destruct x.
apply (inr (b (eq_inla_inltt a0))).
apply (inl (a (eq_inra_inrtt b0))).
Defined.
Definition eq_sum_sigT {A} {B} (x: A + B):
eq x (sigT_to_sum (sum_to_sigT x)).
Proof.
by case x.
Defined.
But I'm in trouble in proving the other side, basically because I don't manage to establish equality between the different x and p involved in the following proof:
Definition eq_sigT_sum {A} {B}
(y: sigT (fun x: Boole => prod ((eq x (inrb tt)) -> A) (eq x (inlb tt) -> B))) : eq y (sum_to_sigT (sigT_to_sum y)).
Proof.
case: (sum_to_sigT (sigT_to_sum y)).
move=> x p.
destruct y.
destruct x.
destruct p.
Defined.
Does anyone know how I can prove the latter lemma?
Thanks for the help.
As bizarre as this sounds, you cannot prove this result in Coq's theory.
Let's call the type sigT (fun x => prod (eq x (inrb tt) -> A) (eq x (inlb tt) -> B)) simply T. Any element of T has the form existT x (pair f g), where x : Boole, f : eq x (inrb tt) -> A, and g : eq x (inlb tt) -> B. To show your result, you need to argue that two expressions of type T are equal, which will require at some point proving that two terms f1 and f2 of type eq x (inrb tt) -> A are equal.
The problem is that elements of eq x (inrb tt) -> A are functions: they take as input a proof that x and inrb tt are equal, and produce a term of type A as a result. And sadly, the notion of equality for functions in Coq is too weak to be useful in most cases. Normally in math, we would argue that two functions are equal by showing that they produce the same results, that is:
forall f g : A -> B,
(forall x : A, f x = g x) -> f = g.
This principle, usually known as functional extensionality, is not available in Coq by default. Fortunately, the theory allows us to safely add it as an axiom without compromising the soundness of the theory. It is even available to us in the standard library. I've included here a proof of a slightly modified version of your result. (I've taken the liberty of using the ssreflect library, since I saw you were using it too.)
From mathcomp Require Import ssreflect ssrfun ssrbool eqtype.
Require Import Coq.Logic.FunctionalExtensionality.
Section Iso.
Variables A B : Type.
Inductive sum' :=
| Sum' x of x = true -> A & x = false -> B.
Definition sum'_of_sum (x : A + B) :=
match x with
| inl a =>
Sum' true
(fun _ => a)
(fun e : true = false =>
match e in _ = c return if c then A else B with
| erefl => a
end)
| inr b =>
Sum' false
(fun e =>
match e in _ = c return if c then A else B with
| erefl => b
end)
(fun _ => b)
end.
Definition sum_of_sum' (x : sum') : A + B :=
let: Sum' b f g := x in
match b return (b = true -> A) -> (b = false -> B) -> A + B with
| true => fun f _ => inl (f erefl)
| false => fun _ g => inr (g erefl)
end f g.
Lemma sum_of_sum'K : cancel sum_of_sum' sum'_of_sum.
Proof.
case=> [[]] /= f g; congr Sum'; apply: functional_extensionality => x //;
by rewrite (eq_axiomK x).
Qed.
End Iso.

extracting evidence of equality from match

I am trying to make the following work:
Definition gen `{A:Type}
{i o: nat}
(f: nat -> (option nat))
{ibound: forall (n n':nat), f n = Some n' -> n' < i}
(x: svector A i) (t:nat) (ti: t < o): option A
:= match (f t) with
| None => None
| Some t' => Vnth x (ibound t t' _)
end.
In place of last "_" I need an evidence that "f t" is equals to "Some t'". I could not figure out how to get it from the match. Vnth is defined as:
Vnth
: ∀ (A : Type) (n : nat), vector A n → ∀ i : nat, i < n → A
Writing this function requires an instance of what is known as the convoy pattern (see here). I believe the following should work, although I can't test it, since I don't have the rest of your definitions.
Definition gen `{A:Type}
{i o: nat}
(f: nat -> (option nat))
{ibound: forall (n n':nat), f n = Some n' -> n' < i}
(x: svector A i) (t:nat) (ti: t < o): option A
:= match f t as x return f t = x -> option A with
| None => fun _ => None
| Some t' => fun p => Vnth x (ibound t t' p)
end (eq_refl (f t)).